2017
DOI: 10.3892/ol.2017.7221
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‑based quantitative proteomic analysis and bioinformatics study of proteins in retinoblastoma

Abstract: Abstract. The aim of the present study was to analyze proteins in the aqueous humor (AH) of patients' retinoblastoma (RB), and investigate their potential role in RB using the comparative proteomic technique of isobaric tags for relative and absolute quantitation (iTRAQ) coupled with offline two-dimensional liquid chromatography-tandem mass spectrometry. A total of 0.1 ml AH was collected from 10 children with RB (mean age, 3.8 years; range, 2-5 years) and patients with senile cataracts (mean age, 70.4 years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The samples that were cultivated under optimal conditions were used as a reference to identify the differential expression. We defined DEPs as those up-expressed > 1.2 or down-expressed < 0.8 with a p- value < 0.05 ( t -test, multiple testing correction) under each stress condition, which is the cutoff commonly used for iTRAQ-based proteomics analysis of both prokaryotes and eukaryotes ( Wang et al, 2016 , 2020 ; Cheng et al, 2017 ; Hou et al, 2019 ; Li et al, 2019 ). The details of the specific growth rates, maximum growth yields, and number of DEPs under each condition are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The samples that were cultivated under optimal conditions were used as a reference to identify the differential expression. We defined DEPs as those up-expressed > 1.2 or down-expressed < 0.8 with a p- value < 0.05 ( t -test, multiple testing correction) under each stress condition, which is the cutoff commonly used for iTRAQ-based proteomics analysis of both prokaryotes and eukaryotes ( Wang et al, 2016 , 2020 ; Cheng et al, 2017 ; Hou et al, 2019 ; Li et al, 2019 ). The details of the specific growth rates, maximum growth yields, and number of DEPs under each condition are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…One study examined levels of uric acid 44. Three studies analyzed proteins in AH, including protein concentrations25,31 and protein analysis 27. One study examined the cytokines, chemokines, matrix metalloproteinases, and acute-phase protein concentrations 45.…”
Section: Resultsmentioning
confidence: 99%
“…One study further assessed AH proteins by using the comparative proteomic technique of isobaric tags for relative and absolute quantitation coupled with offline two-dimensional liquid chromatography-tandem mass spectrometry 27. A total of 83 proteins that were expressed differently between the controls and patients' AH samples were identified using isobaric tags for relative and absolute quantitation analysis, including pigment epithelium-derived factor (PEDF) and retinoic acid 6 (STRA6) 27. The study revealed that the expression level of PEDF was lower in Rb than that in control samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al, on the other hand, analyzed aqueous humour samples from RB patients and compared them with aqueous humour samples from patients without intraocular cancer using the comparative proteomic technique of iTRAQ coupled with offline two-dimensional liquid chromatography-tandem mass spectrometry. A total of 83 proteins were identified to be differentially expressed, of which 44 were upregulated and 39 downregulated in the RB group (22). Assisted by the DAVID bioinformatics resource, protein expression in RB has been implicated in endopeptidase inhibitory activity, peptidase inhibitor, enzyme inhibitor, serine-type endopeptidase inhibitor, structural molecule, lipid binding and carbohydrate binding activities (22).…”
Section: Discussionmentioning
confidence: 99%